Phytochemical analysis and in vitro biological activity assessment of extracts from Micromeria myrtifolia - ŞENER, TARIK EMRE; ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2024)
In this study, the antioxidant capacity, the effect on anti-acetylcholinesterase and anti-urease enzyme inhibition, and kidney stone-reducing effects of different extracts from M.myrtifolia. In addition, the phytochemical content of the bioactive methanol extract was analyzed by HPLC-DAD. The methanol extract showed strong DPPH (IC50:0.036 mg/mL) radical scavenging, Cu (II) ion (6.535 mmTroloxE) and Fe3+ (6.476 FeSO4) ion reducing antioxidant activity compared to other extracts. The methanol extract contained the highest amount of phenolic (400 mgGAE) and flavonoid (2.519 QuE) compounds. Moreover, the methanol extract had significant anticholinesterase (78.935%), anti-urease (71.014%) and calcium oxalate anti-crystallization (18.22%, 37.427%) activities. The findings show that all extracts exhibited varying amounts of antibacterial activity against Staphylococcus aureus. The bioactive methanol extract contained rosmarinic acid (31.35 µg), quercetin (12.99 µg) and chlorogenic acid (3.55 µg). The analyzed compounds are thought to contribute significantly to the pharmacological effect of the methanol extract.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Yaşam Bilimleri (Life); Sosyal Bilimler (Soc); Mühendislik; Farmakoloji Ve Toksikoloji; Sosyal Bilimler Genel; Mühendislik Çevre; Toksikoloji; Kamu Çevre Ve İş Sağlığı; Engineering Computing & Technology (Eng); Life Sciences (Life); Social Sciences (Soc); Engineering; Pharmacology & Toxicology; Social Sciences General; Engineering Environmental; Toxicology; Public Environmental & Occupational Health; Kirlilik; Fizik Bilimleri; Halk, Çevre ve İş Sağlığı; Sağlık, Toksikoloji ve Mutajenez; Pollution; Physical Sciences; Public Health, Environmental and Occupational Health; Health, Toxicology and Mutagenesis; biological activity; HPLC-DAD; Micromeria myrtifolia